2022
DOI: 10.3748/wjg.v28.i31.4376
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative contrast-enhanced computed tomography-based radiomics model for overall survival prediction in hepatocellular carcinoma

Abstract: BACKGROUND Hepatocellular carcinoma (HCC) is the most common primary liver malignancy with a rising incidence worldwide. The prognosis of HCC patients after radical resection remains poor. Radiomics is a novel machine learning method that extracts quantitative features from medical images and provides predictive information of cancer, which can assist with cancer diagnosis, therapeutic decision-making and prognosis improvement. AIM To develop and validate a contrast-enh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Liu et al [ 28 ] developed a DL-radiomics model using preoperative contrast-enhanced ultrasound images for early-stage HCC to predict progression-free survival after ablation or surgical resection. And some scholars used the radiomics model based on single-center CT images to predict OS of HCC patients after surgery [ 29 , 30 ]. The performance of these models was similar to that of our study, while the generalization performance of the model needs to be further validated with limitations of the single-center study.…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al [ 28 ] developed a DL-radiomics model using preoperative contrast-enhanced ultrasound images for early-stage HCC to predict progression-free survival after ablation or surgical resection. And some scholars used the radiomics model based on single-center CT images to predict OS of HCC patients after surgery [ 29 , 30 ]. The performance of these models was similar to that of our study, while the generalization performance of the model needs to be further validated with limitations of the single-center study.…”
Section: Discussionmentioning
confidence: 99%
“…Prognostic models based on radiomic features combined with clinicopathological features have been recognized by an increasing number of studies. For example, Deng et al ( 25 ) predicted the OS of individuals with HCC following radical hepatectomy by incorporating AFP, neutrophil-to-lymphocyte ratio (NLR), and radiomic features into a nomogram. The AUC of the ROC curve for 1-, 3-, and 5-year OS prediction was 0.850, 0.791, and 0.823 in the training cohort and 0.905, 0.884, and 0.911 in the validation cohort, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Deng et al [43] demonstrated that radiomics models hold an advantage in predicting overall survival (OS) following radical resection. By constructing a radiomics prediction model using pre-surgery CT images, they achieved AUCs of 0.905, 0.884, and 0.911 for predicting 1-year, 3-year, and 5-year OS, respectively, in the validation cohort.…”
Section: Surgical Therapy For Malignant Liver Tumorsmentioning
confidence: 99%